Pemanfaatan Berbagai Jenis Pupuk Hayati pada Budidaya Tanaman Jagung(Zea mays. L) Efisien Hara di Lahan Kering Marginal - Yopie Moelyohadi; M. Umar Harun; Renih Hayati; Nuni Gofar (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Moelyohadi et al., 2012. The Use of Various Types of Biofertilizers on Cultivation of Nutrient Efficient Corn Genotypes(Zea mays L. in Marginal Dry Land. JLSO 1(1):31-39.The study aimed at obtaining nutrient efficient corn genotypes that give the best response to various types of biological fertilizers at low-level doses of chemical fertilizer in marginal drylands. This study was conducted in the field trials of Agro Techno Park (ATP), the Ministry of Research and Technology, South Sumatra from May to September 2011. The experimental design used was SplitPlotdesign with three replications. The main plot treatments consisted of: (H0): without biofertilizer, (H1): biofertilizer:-mycorrhizae and (H2): BPF biological fertilizers. Subplot treatments, consisting of three corn genotypes for the selection of efficient nutrient properties, are genotypes B-41 (G1), L-164 (G2), S-194 (G3) and onehybrid variety:BISI-816 (G4) as agenotypecomparator. Alltreatmentunitswere givenlow dosesof chemicalfertilizerthat is 50% of theATPstandarddose(200kgUrea, SP-36 50kgand 25kgKClha-1). The results showed that mycorrhizal fertilizer produced the highest corn production, which is 6.08 ton dry seed / acre and genotype B-41 shows a more adaptive growth in marginal dry land with a production of 7.27 tons of dry seed /acre and the combined treatment of mycorrhizal fertilizer and genotype B-41 gave the highest production of 8.57 tons of dry seed / acre